Transformation of adenocarcinoma to squamous cell carcinoma as a source of EGFR-TKI resistance: A case report and literature review - Xi, Yun-Zhu; Xie, Li; Tan, Xiao-Wu; Zeng, Sai-Li (Frontiers in Oncology, 2022)
In general, non-small cell lung cancer patients with epidermal growth factor receptor (EGFR) mutations respond to tyrosine kinase inhibitors (TKIs). However, most patients experience resistance within 1-2 years after treatment. The histological explanation for the acquired resistance is that malignant transformation occurs during cancer treatment. To date, the transformation from adenocarcinoma to squamous cell carcinoma associated with EGFR-TKI use remains poorly reported. We report a case of stage IV lung adenocarcinoma with EGFR mutations that converted to squamous cell carcinoma due to long-term administration of EGFR-TKIs. This report strengthens histological evolution as a source of acquired drug resistance.